PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA MELALUI KEPUASAN KERJA KARYAWAN PADA BANK ARTHA GRAHA INTERNATIONAL Tbk PEKANBARU - Eka Riswanto; Samsir '; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims at analyzing the influence of organizational commitment through employees satisfaction at Artha Graha International Bank Tbk Pekanbaru. The sample of this research is 107 employees of the Bank. Analysis method used is descriptive analysis method by testing variables, doubled regression and path analysis. From the results of the testing conducted, it is seen the influence of the variable of organizational commitment on job satisfaction. There is positive influence of the variable of organizational commitment toward employees’ performance. For indirect influence, the influence of organizational commitment on employees’ performance through job satisfaction is smaller than direct influence. Hypothesis states that "The better the organizational commitment, the better employees’ job satisfaction of Artha Graha International Bank Tbk Pekanbaru", "The better the job satisfaction, the better the performance of employees of Artha Graha International Bank Tbk Pekanbaru" and last hypothesis "The better the organizational commitment, the better performance through employees’ satisfaction of Artha Graha International Bank Tbk Pekanbaru" can be accepted because indirect influence of organizational commitment to performance through satisfaction is bigger than the direct influence of organizational commitment to employees’ performance.Keyword : Organizational Commitment, Job Satisfaction and Employee Performance.